2019
DOI: 10.1101/611962
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparing and Validating Automated Tools for Individualized Electric Field Simulations in the Human Head

Abstract: Comparing electric field simulations from individualized head models against in-vivo recordings is important for direct validation of computational field modeling for transcranial brain stimulation and brain mapping techniques such as electro-and magnetoencephalography. This also helps to improve simulation accuracy by pinning down the factors having the largest influence on the simulations. Here we compare field simulations from four different automated pipelines, against intracranial voltage recordings in an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…We believe that overall simulation errors in the observed range are currently still acceptable, given that other error sources such as segmentation errors [38,45], the uncertainty of the values of the ohmic tissue conductivities [46], putative inaccurate or simplified modeling of the of TMS coil or TES electrode properties and positions [7] can cause errors in or above this range. For example, in a recent study [46], we found standard deviations in maximum electric field values due to uncertainty in tissue conductivities to be around 5% of the mean value in TMS, but around 20% of the mean value in TES, and in another study [45], we found the TES electric fields obtained from different head segmentation tools to vary up to 40%. This suggest that future efforts to increase simulation accuracy will have to commonly account for all these factors, rather than focusing on improving the numerical accuracy alone.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that overall simulation errors in the observed range are currently still acceptable, given that other error sources such as segmentation errors [38,45], the uncertainty of the values of the ohmic tissue conductivities [46], putative inaccurate or simplified modeling of the of TMS coil or TES electrode properties and positions [7] can cause errors in or above this range. For example, in a recent study [46], we found standard deviations in maximum electric field values due to uncertainty in tissue conductivities to be around 5% of the mean value in TMS, but around 20% of the mean value in TES, and in another study [45], we found the TES electric fields obtained from different head segmentation tools to vary up to 40%. This suggest that future efforts to increase simulation accuracy will have to commonly account for all these factors, rather than focusing on improving the numerical accuracy alone.…”
Section: Discussionmentioning
confidence: 99%
“…Blind parameter optimization inevitably enhances match; in our principled approach we tested the emulated-CSF value determined systematically in concentric-sphere. The application of this data set is not without noise and methodological nuance [44], and the method of segmentation and other modeling assumption [27] would impact the role of the CSF compartment. In any case, broader consideration of changing modeling pipelines is explicitly outside our scope.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, for neurostimulation purposes only, there is SIMNIBS [82] and ROAST [83]. A comparison between these packages has been presented in [84]. The main differences in the results between those two packages were found to be caused by differences in segmentation by the two packages.…”
Section: Software Implementationsmentioning
confidence: 99%